Transformasi Mutu Pendidikan di Sekolah: dalam Menanggulangi Krisis Pembelajaran - Hizamul Fikri Aditama; Dwi Frengky Stiawa (Jurnal Manajemen dalam Pendidikan, 2025)
Education is one of the main pillars of a nation’s development. In Indonesia, the quality of education, particularly at the secondary school level, faces significant challenges that have led to a learning crisis. This study aims to analyze the transformation of education quality in secondary schools in response to the learning crisis influenced by the COVID-19 pandemic, technological changes, and disparities in educational quality across regions. The research employs a qualitative approach with a descriptive design, combining data collection techniques through in-depth interviews, observations, and documentation to obtain a comprehensive picture of challenges, policies, and practices in the field. The findings reveal that the application of digital technology in learning, the strengthening of competency-based curricula, and the improvement of teacher competence have contributed to progress in enhancing education quality. However, gaps in access to technology and the lack of readiness among teachers to manage technology-based learning remain significant issues. The study also found that although educational policies have been updated, the main challenge lies in uneven implementation and difficulties in adapting to local needs. The implications of this research highlight the crucial role of the government in addressing disparities in access and supporting continuous teacher training to strengthen educational transformation. Furthermore, the study opens opportunities for further research on holistic solutions that incorporate psychological, social, and cultural aspects to improve the quality of education in Indonesia.